The Efficacy of Mycosorb in Broiler Diets Contaminated with Low Doses of Aflatoxin B1 - Catootjie Lusje Nalle; Max Arthur Julian Supit; Ignasius Juncen Riu Bere; Roni Hawu (Buletin Peternakan, 2021)
The objective of the present study was to evaluate the efficacy of Mycosorb in broiler diets containing a low level of aflatoxin B1 (AFB1). A total of 200 male broiler chicks (Lohmann) were randomly distributed into 20 pens (10 birds/pen). The experimental design used was a 2 x 2 factorial completely randomized design with two main factors which were the AFB1 levels (non-detectable level; 2.58 ppb) and mycotoxin binder (MB) (0 and 0.15% Mycosorb), respectively. The treatments were control diet (P1), control diet + MB (P2), 2.58 ppb AFB1 diet (P3), and 2.58 ppb AFB1 diet + MB (P3). The AFB1 diets were formulated by replacing the whole proportion of fresh corn with moldy corn containing 4.22 ppb AFB1. The results showed that except for the digestibility coefficient of crude fat (DCCF), AL x MB interaction was not significant (P>0.05) for the growth performance and DCCP. The AFB1 levels (AL) improved (P<0.001) feed intake (FI), feed conversion ratio (FCR), and reduced the DCCF of broilers. The AFB1 levels enhanced the body weight gain (BWG) of growing broilers, but it did not augmented (P>0.05) the BWG of starter broilers. The digestibility coefficient of crude protein was not influenced (P>0.05) by the AFB1 levels. DCCF of broilers who received AFB1 diets were lower (P<0.05) than that of the control diet. Mycosorb did not affect (P>0.05) all variables measured. In conclusion, 1) except for DCCF, AFB1 levels x MB interaction did not improve growth performance and DCCP;  2) the AFB1 level of 2.58 ppb in the diets increased FI and BWG of broilers, but reduced the feed efficiency and DCCF; and 3) Mycosorb did not improve all variables measured.